Effect of Acupuncture Treatment on Level of Serum Interferon (IFN)-γ in BALB/c Model of Leishmania Major Infection - Mahshid Shakibapour; Shervin Ghaffari Hoseini; Mohsen Mahmoodi; Fatemeh Rostami; Seyed Hossein Hejazi (مجله دانشکده پزشکی اصفهان, 2013)
Background: Cutaneous leishmaniasis (CL) is an endemic parasitic disease in Iran. Current treatments for the disease are not satisfying, have many side effects and are expensive. The healing effect of T-helper 1 (Th1) immune response, especially interferon (IFN)-γ secretion in CL has been previously documented. It has been shown that acupuncture, a traditional Chinese medicine, also might activate Th1 immune response. In this study, the effect of acupuncture on serum level of IFN-γ in experimental CL of BALB/c mice was investigated.